Genital herpes: modern views and prospects for the treatment - Aleksey A. Khryanin; German Yu. Knorring (IP Berlin A.V., 2020)
The review focuses on the clinical and epidemiological characteristics of herpes viral infection, in particular genital herpes. The current treatment options for recurrent genital herpes are presented. A detailed description of valaciclovir is given.